아동 디지털 리터러시 함양을 위한 영어교육환경과 수업역량 연구 - 장성임; Sung-im Jang; 김혜영; Heyoung Kim (Multimedia-Assisted Language Learning, 2024)
Digital literacy (DL) is a student-centered learning competency, often referred to as ‘new literacy’. This study aims to investigate digital environment for early childhood English education and the DL competency of English teachers. A survey was conducted with 249 Korean English teachers in early childhood education institutions. The questionnaire included class profile, digital tools and programs utilized in their classrooms, and instructional methods for integrating technology. The results indicate that early childhood learning environment is generally conducive to developing DL. Teachers reported using an average of four devices and more than three programs during English classes, dedicating about half of their class time to teaching storybooks, the alphabet and phonics. However, the approach to using technology remains teacher-centered, primarily involving material presentation to children. There is a lack of technology-assisted games, activities, and projects, resulting in limited opportunities for students to engage directly with devices and programs. Regarding DL teaching competency, teachers rated their skills below ‘occasionally (M=2.97)’ Except for ‘authenticity’, their competency in all other areas fell below 3.0 indicating minimal opportunities for students to develop DL. It is essential for educational authorities or early childhood institutions to monitor and enhance their English curricula and teacher competencies. DL workshops and teacher training programs should be provided for kindergarten English teachers.